Problem of Typology of Intertextual Inclusions and Their Role in Intertext Structure (by Material of Magazine and Newspaper Articles) - O. V. Ryabukha; A. V. Troshina (Научный диалог, 2018)
The problem of typology of intertextual inclusions and their role in a text structure is considered. To denote semantically rich inclusions linking the text with the precedent text and requiring the reader to make efforts to recognize these links, the term intext , which was proposed by P. Kh. Torop, is used. The views of linguists on understanding of the category “text” and relationship between the precedent text and the recipient text are presented. Definitions of intertextuality and intext are given. Classification of intext functions is proposed. The relevance of the study is due to the lack of study of the functioning of intexts in the framework of magazine and newspaper articles. The novelty of the work lies in the analysis of functions of intexts on the material of modern press. The analysis reveals the most common intextic functions in such articles: text-generating / constructive, commenting, ironic, expressive, poetic, referential and appellate. Attributed and non-attributed intexts are distinguished and the importance of presence or absence of there marking is discusses. Differences in volume of used intexts, which can consist of one word or represent a broad intertextual inclusion, are revealed. Particular attention is paid to the use of allusions and quotations, performing the function of increment of meaning in intertexts.